2z-9=-5-2(2z+8)

Simplify each term.

Apply the distributive property.

2z-9=-5-2(2z)-2⋅8

Multiply 2 by -2.

2z-9=-5-4z-2⋅8

Multiply -2 by 8.

2z-9=-5-4z-16

2z-9=-5-4z-16

Subtract 16 from -5.

2z-9=-4z-21

2z-9=-4z-21

Add 4z to both sides of the equation.

2z-9+4z=-21

Add 2z and 4z.

6z-9=-21

6z-9=-21

Add 9 to both sides of the equation.

6z=-21+9

Add -21 and 9.

6z=-12

6z=-12

Divide each term in 6z=-12 by 6.

6z6=-126

Cancel the common factor of 6.

Cancel the common factor.

6z6=-126

Divide z by 1.

z=-126

z=-126

Divide -12 by 6.

z=-2

z=-2

Solve for z 2z-9=-5-2(2z+8)